مدى فاعلية نظام تقييم الأداء الوظيفي في الشركات الصناعية بمحافظة ظفار - Muslim Mubarak Kshob, K.; Siti Rugayah, S.R.; Sammari, N. (Universiti Sains Islam Malaysia, 2024)
The objective of the research is to evaluate the effectiveness of the evaluation system of the workers’ performance in some industrial companies operating in Dhofar governorate, and to identify the means and methods used in the evaluation process and their impact on improving the employees’ performance. The problem is the employees’ evaluations can be characterized as non-objective; and influenced by personal relationships between the evaluator and the staff. The research community consists of (101) administrative employees at three private sector companies in the Governorate; were all selected as study sample. The analytical descriptive method were used to achieve the research objectives, and SPSS was used to analyze the data. The findings revealed that a strong and positive relationship between the performance evaluation interview and the performance appraisal system applied in the surveyed institutions. As well as between the evaluator's role in the performance appraisal process and the applicable performance appraisal system. And that there was no relationship between the performance appraisal problems of the evaluator and the performance appraisal system applied to those institutions. The researcher recommended the need to review the evaluation results by the senior departments, not only by the supervisors; to ensure more accuracy in evaluations.